2022
DOI: 10.1177/01430343221137717
|View full text |Cite
|
Sign up to set email alerts
|

Towards best practice during COVID-19: A responsive and relational program with remote schools to enhance the wellbeing of Aboriginal and Torres Strait Islander students

Abstract: Purpose From 2018, the Schools Up North (SUN) programme worked with three remote Australian schools to enhance their capability and resilience to support the wellbeing and mental health of Aboriginal and Torres Strait Islander students and staff. This paper explores the implementation of SUN during the first two years of COVID-19 (2020–2021). Method: Using grounded theory methods, school staff, other service providers and SUN facilitators were interviewed, with transcripts and programme documents coded and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In this regard—and following from the Theron et al (2022) paper on this themed issue—there is likely to be merit in SPs focus on developing teachers’ capacity to better support students (especially girl students) to be school engaged. Similarly, and as reported in the McCalman et al (2022) paper on this themed issue, there is resilience-enabling value in enhancing teacher capability to provide contextually relevant mental health support. To that end, SPs could facilitate teacher professional development to better understand, engage and support students (e.g., by training of teachers in Social Emotional Learning [SEL] and trauma-informed approaches; Abramson, 2022).…”
Section: Schools As Caring Communities With a Commitment To Student R...mentioning
confidence: 62%
See 4 more Smart Citations
“…In this regard—and following from the Theron et al (2022) paper on this themed issue—there is likely to be merit in SPs focus on developing teachers’ capacity to better support students (especially girl students) to be school engaged. Similarly, and as reported in the McCalman et al (2022) paper on this themed issue, there is resilience-enabling value in enhancing teacher capability to provide contextually relevant mental health support. To that end, SPs could facilitate teacher professional development to better understand, engage and support students (e.g., by training of teachers in Social Emotional Learning [SEL] and trauma-informed approaches; Abramson, 2022).…”
Section: Schools As Caring Communities With a Commitment To Student R...mentioning
confidence: 62%
“…The papers in this special issue provide some pointers to how the adults associated with a school community could form a caring whole and support the resilience of students challenged by various forms of marginalization. While the geographical contexts reported in the papers on this resilience-themed issue vary (e.g., students from rural/urban USA [Chatlos et al, 2022; Goodwin et al, 2022]; remote Australia [McCalman et al, 2022], and South Africa [Mohangi, 2022; Pillay, 2022; Theron et al, 2022]), as do the marginalization experiences (e.g., disability or special education needs ([Chatlos et al, 2022; Goodwin et al, 2022], rurality/remote location [Chatlos et al, 2022; McCalman et al, 2022], visible minority [Goodwin et al, 2022], and/or structural disadvantage [Mohangi, 2022; Pillay, 2022; Theron et al, 2022]), the capacity of caregivers and school staff to support student resilience during the pandemic was invariant. For instance, Goodwin et al (2022) reported mental health benefits for American elementary school students and their caregivers when elementary school teachers and caregivers shared a sense of supportive connectedness.…”
Section: Schools As Caring Communities With a Commitment To Student R...mentioning
confidence: 99%
See 3 more Smart Citations